DAMPAK TACTICAL PERIODIZATION DAN POSISI PEMAIN TERHADAP RESPON FISIOLOGI - Kartono Pramdhan, - (2021)
ABSTRACT IMPACT OF TACTICAL PERIODIZATION AND PLAYER'S POSITION ON PHYSIOLOGICAL RESPONSE Tactical Periodization has the principle that each exercise discusses the four moments that make up the game of football, becoming the principles and sub-principles of the game. Thus, training is a mechanism that allows players to understand the way the coach is trying to play. A football training is certainly a concept rather than a coach to create a more specific training model for a match. The purpose of this study was to examine the effect of tactical periodization and the player's position on physiological responses. The research method used an experimental method with a factorial design. Participants in this study were the Indonesian league elite team using simple random sampling technique. The instrument in this study was to determine the physiological response consisting of distance, work rate, hate rate average, maximum hate rate, avarage speed, maximum speed, body load using a GPS-based Catapult. The significance test used two-way MANOVA. The results of the study concluded that tactical periodization and the position of the players had an effect on the physiological response of the elite Indonesian soccer team. The findings of this study are that there is an interaction between tactical periodization and the position of the players to the physiological response of the elite Indonesian football team, from the post hoc results using the Tukey tactical periodization test with the position of the back, middle and front players there is no difference in physiological responses in the elite team of the experimental group 1 and the experimental group elite team 2. Keywords: tactical periodization, player position, physiological response.